1970. SARS-CoV-2 T-cell specific responses in allogeneic hematopoietic stem cell transplant recipients after second and third dose of BNT162b2 mRNA vaccine. (15th December 2022) - Marco, Iannetta; Spalliera, Ilaria; Mallegni, Flavia; Mercante, Lisa; Imeneo, Alessandra; Crea, Angela; Lorenzo, Andrea Di; Campogiani, Laura; Malagnino, Vincenzo; Angelis, Gottardo De; Cerretti, Raffaella; Andreoni, Massimo; et al.
Abstract: Background: Cell-mediated immunity (CMI) after anti-Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV)-2 vaccines has been poorly explored in recipients of allogeneic hematopoietic stem-cell transplantation (HSCT), especially with regard to the 3 rd dose (booster). Aim of the study was to assess the specific T-cell responses before and after the 3 rd dose of BNT162b2 mRNA vaccine in a cohort of allogeneic HSCT recipients, and compare it with healthy donors (HD). Methods: Allogenic HSCT recipients and HD were enrolled before receiving the 3 rd dose of BNT162b2 mRNA vaccine. Whole blood for T-cell specific responses was collected before (T1) and 8 weeks after (T2) the booster administration. T-cell responses were assessed with an Interferon (IFN)-γ release assay (IGRA), after overnight stimulation of heparin whole blood with pools of lyophilized peptides, covering the immunodominant sequence of the Spike (S) protein. IFN-γ production was assessed with an enzyme linked immunosorbent assay (ELISA). Statistical analysis was performed with GraphPadPrism. Results: 14 HSCT recipients (8M, 6F) and 15 HD (7M, 8F) were enrolled (table 1). Median age was 47 [39-59] and 41 [31-48] years in the HSCT and HD groups, respectively. Time between the vaccine 2 nd dose and T1 was significantly longer in HD than HSCT recipients (p< .001), while the time between T1 and T2 did not differ between the two groups. SARS-CoV-2 S specific T-cell responses at T1 were inferior in HSCT recipients compared to HD (median IFN-γ production: 463 vs 231 ng/ml, respectively), although the difference did not reach the statistical significance. No differences were observed at T2. In a before-after analysis, SARS-CoV-2 S specific T-cell responses were significantly increased in HSCT recipients at T2 compared to T1 (median IFN-γ production: 267 vs 881 ng/ml, p=0.02) (Figure 1). At T1, 3 HSCT recipients showed very low or no IFN-γ production, while at T2 only 1 patient still had undetectable IFN-γ production after S peptide stimulation. Table 1: Clinical characteristics of allo-HSCT recipients and HD HSCT: hematopoietic stem-cell transplantation; IQR: interquartile range; ALL: acute lymphoblastic leukemia; AML: acute myeloid leukemia; MDS: myelodysplastic syndrome; T-ALL: T-cell acute lymphoblastic leukemia; AA: aplastic anemia; PMF: primary myelofibrosis; MUD: matched unrelated donor; MMUD: mismatched unrelated donors; NA: not applicable; ns: not significant. Figure 1: IFN-γ Production after Spike peptide stimulation of whole blood from allogenic HSCT recipients and HD. Comparison of IFN-γ production after Spike peptide stimulation of whole blood in allogenic HSCT recipients and HD at T1 (1.A) and T2 (1.B) (before and after BNT162b2 mRNA vaccine 3rd dose, respectively). Before-after representation of IFN-γ production after Spike peptide stimulation in HD and allogenic HSCT recipients (1.C). Conclusion: SARS-CoV-2 IGRA represents a useful tool to assess CMI, also in immunocompromised hosts. An additional 3 rd BNT162b2 mRNA vaccine booster dose seems to enhance CMI in allogenic HSCT recipients. Further studies are needed to evaluate the duration of SARS-CoV-2 CMI in HSCT recipients compared to HD. Disclosures: All Authors : No reported disclosures.